2019
DOI: 10.17507/jltr.1004.04
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reading for University EFL Learners: Its Effects and Both Teachers' and Learners' Views

Abstract: The effect of reading on general communicative competence remains a focus of second language acquisition research. Extensive reading, in particular, provides rich input and helps learners acquire languages. Research has provided findings that support the value of extensive reading (ER); however, there is scant evidence to date showing the relationship of extensive reading to overall competence and, particularly, writing competence. The present study investigated the relationship of ER to overall English langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…A greater proportion of learners from different parts of the world have made social recognition their reason for learning a second language. The findings of this study along with previous studies such as Wang & Ho (2019) which revealed that learners tended to hold a favorable attitude toward extensive reading and perceive it to be important and effective learning, having confidence in its effect. Similar findings from Yılmaz et al (2020) also indicated that ER increased their self-confidence in learning English as they overcame fear of making mistakes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A greater proportion of learners from different parts of the world have made social recognition their reason for learning a second language. The findings of this study along with previous studies such as Wang & Ho (2019) which revealed that learners tended to hold a favorable attitude toward extensive reading and perceive it to be important and effective learning, having confidence in its effect. Similar findings from Yılmaz et al (2020) also indicated that ER increased their self-confidence in learning English as they overcame fear of making mistakes.…”
Section: Discussionsupporting
confidence: 77%
“…The study's outcome exhibited that the students had positive perceptions toward ER practices and considered if ER is a reading activity for pleasure and information search where they can read material without any restraint. The subsequent study is from Wang & Ho (2019), who investigated the relationship of ER to overall English language competence both teachers' and students' views about its implementation. The participants were 190 Taiwanese university freshman and three English instructors.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, students could broaden their vocabulary after participating in an extensive reading program [6]. Gaining statistically significant in listening, reading, and writing test scores after one year of implementing extensive reading [7]. Those previous studies focused primarily on extensive reading activity that took place offline.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly true for extensive reading practices that promote enjoyment (Anindita, 2020;Dwyer et al, 2014). Wang and Ho (2019) added that extensive reading could develop language abilities, reading habits, and positive attitudes. Frequent reading enhances reading comprehension, vocabulary, writing fluency, and precision.…”
Section: Introductionmentioning
confidence: 99%